Empfindsame Urbanität: zur kulturellen Polyphonie der Briefe über Mannheim (1791) von Sophie von La Roche - Kühlmann, Wilhelm (Daphnis, 2022)
Abstract Sophie von La Roche’s ‘Letters on Mannheim’ (1791) are examined in the context of their origin as well as in the wide and complex field of epistolary forms, purposes and themes. The study analyses La Roche’s autobiographical, journalistic and cultural-pedagogical claim in these letters as well as its hybrid character as a work of literature, which oscillates between fictionality and factuality. Even though this document of the late Enlightenment deals with important personalities, landmarks and institutions of Mannheim (such as the theatre), everyday questions of behavioural culture and intellectual orientation are repeatedly addressed. Thus, the multipurpose nature of public letter writing in late eighteenth century will be demonstrated with a characteristic example.
Gesehen am 01.09.2022
Keywords: La Roche, Sophie von -- 1730-1807; Geschichte 1700-1800; Mannheim